A quasi-symmetric formulation for contact between deformable bodies - Fourment, Lionel (European Journal of Computational Mechanics, 2008)
In the frame of contact issues between 3D deformable bodies with non-matching finite element discretizations of possibly very different mesh sizes, a quasi-symmetric formulation is proposed to obtain satisfactory results whichever body is selected as master or slave. This approach is not based on usual mortar elements in order to avoid the creation of an additional integration surface. It draws its inspiration from a symmetric treatment of the contact conditions, where the formulation is made compatible by replacing the Lagrange multiplier of the master body by the projection of the slave one. Numerical results are obtained within the FORGE3® finite element software. Numerous 3D test cases numerically show that this approach actually solves the main issues of contact between deformable bodies, in a rather simple way.